Peran Aliansi Strategis terhadap Pengembangan Produk Baru - Noor Aziz (Universitas Muria Kudus, 2018)
Research on strategic alliances shows that the external environment that shortens the life cycle of product (PLC), increases R and D costs. The spread of skills and knowledge has led to an increasing need for strategic alliances. At the same time, product development is considered as a key dimension and an important part of corporate effectiveness. Therefore, is this research will examine the relationship of strategic alliances and product development.This research is a case study of Rumah Adat Kudus which aims to (1) analyze the innovation ability of companies which built through strategic alliances influencing product development, (2) analyze the capabilities of manufacturers which built through strategic alliances affecting product development, (3) analyze marketing capabilities which built through strategic alliances affecting product development.This study uses the primary and secondary data. The analysis method used in this study is Multiple Regression Analysis processing by SPSS. This study indicates that the greater innovation capability has a significant positive influence on product development; manufacturer's ability have a significant positive influence on product development; marketing ability has a significant positive influence on product development.